De utryghedsmæssige konsekvenser af udsathed for kriminalitet i Danmark - Rune H. Scherg; Anders Ejrnæs (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article examines the consequences of victimisation in relation to feeling of safety in Denmark.2 Using various statistical models, we address two general questions: First, how do different victimisation patterns affect victims’ feelings of safety, and second, how do victims’ demographic characteristics modify the consequences of victimisation in relation to feelings of safety. We analyse panel data from the Danish Police’s Safety Survey (2014-2018) linked to Danish register data. Although there is an abundance of international research about the victimfear nexus, there are still gaps in our current understanding of this relationship. First, research on the impact of victimization on feelings of safety is often based on cross-sectional studies, which don’t allow for solid causal inferences. Second, potential differences between different groups of victims have not been thoroughly analysed as few studies have had the statistical power to do so. Last, there is a scarcity of Scandinavian studies on the subject. The current article shows that victimization has a consistent effect on feelings of safety. However, the size of the effect is generally moderate and short-lived. The article also demonstrates that the impacts of victimization are disproportionately distributed across different groups of victims.